Analysis of Planning and Budgeting Consistency at the Katingan District Health Office from 2018 to 2020 - Elisawati; Yohanes Joni Pambelum; Fitria Husnacarina (ITScience (Information Technology and Science), 2024)
The inconsistency between planning and budgeting documents at the regional apparatus level is a key issue in Katingan Regency, Central Kalimantan, including at the Katingan Regency Health Office. This study uses a qualitative approach to be able to explain the results of the analysis carried out quantitatively in narrative form. This study was conducted at the Katingan District Health Office, with the analysis method using the Planning and Budgeting Consolidation Matrix (MKPP) to assess the level of consistency, descriptive analysis to analyze the results of interviews and documents of performance achievement assessment results at the Katingan District Health Office. The results of this study indicate that the achievement of financial performance as assessed by the amount of budget saved was in the 2020 budget year. As for the achievement of the performance of the implementation of SPM Health Affairs, the type of infant health service has the highest average criteria for the 3-year observation period. The consistency analysis between the RPJMD and the Katingan District Health Office Strategic Plan shows the lowest level of consistency in 2018 and the highest in 2020 or a very good level of consistency. The consistency analysis between the Katingan District Health Office Strategic Plan and Work Plan shows the lowest level of consistency in 2018 and the highest in 2020 or a very good level of consistency. The analysis of consistency between the RKPD and Renja of the Katingan Regency Health Office shows the lowest level of consistency in 2018 and the highest in 2020 or a very good level of consistency. In this study, factors were found that could affect the consistency/inconsistency of planning and budgeting at the Katingan Regency Health Office, namely: (1) Implementation of e-Government that has not been integrated between the planning and budgeting processes, HR readiness, and the availability of data and information that is not yet accurate for policy formulation and planning; (2) Lack of ability and quality of Health Office HR in planning and budgeting, (3) Changes in regulations and (3) the influence of the budget political process is still strong.